2009
DOI: 10.1371/journal.pgen.1000754
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Organ Expression Profiling Uncovers a Gene Module in Coronary Artery Disease Involving Transendothelial Migration of Leukocytes and LIM Domain Binding 2: The Stockholm Atherosclerosis Gene Expression (STAGE) Study

Abstract: Environmental exposures filtered through the genetic make-up of each individual alter the transcriptional repertoire in organs central to metabolic homeostasis, thereby affecting arterial lipid accumulation, inflammation, and the development of coronary artery disease (CAD). The primary aim of the Stockholm Atherosclerosis Gene Expression (STAGE) study was to determine whether there are functionally associated genes (rather than individual genes) important for CAD development. To this end, two-way clustering w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(162 citation statements)
references
References 59 publications
4
158
0
Order By: Relevance
“…EBF1-deficient mice manifest lipodystrophy characterized by a marked decrease in the amount of white adipose tissue, as well as an increase in yellow adipose tissue in bone marrow compared with wild-type controls (20), consistent with the notion that EBF1 participates in terminal adipocyte differentiation and the initiation of adipocyte development (21). The expression of EBF1 has previously been found to be increased in visceral fat and the atherosclerotic aortic wall (10), and polymorphisms of EBF1 have been shown to be related both to the plasma concentration of low density lipoprotein-cholesterol and to coronary atherosclerosis (11). In this study, we demonstrated that EBF1 was significantly hypomethylated in atheromatous plaque and that the overexpression of EBF1 in HEK293 cells resulted in the increased expression of genes related to cell proliferation (FOXQ1, CCNE1 and PAK1), to inflammatory response (CEBPD), and to cell adhesion (CDH1).…”
Section: Ebf1supporting
confidence: 63%
See 2 more Smart Citations
“…EBF1-deficient mice manifest lipodystrophy characterized by a marked decrease in the amount of white adipose tissue, as well as an increase in yellow adipose tissue in bone marrow compared with wild-type controls (20), consistent with the notion that EBF1 participates in terminal adipocyte differentiation and the initiation of adipocyte development (21). The expression of EBF1 has previously been found to be increased in visceral fat and the atherosclerotic aortic wall (10), and polymorphisms of EBF1 have been shown to be related both to the plasma concentration of low density lipoprotein-cholesterol and to coronary atherosclerosis (11). In this study, we demonstrated that EBF1 was significantly hypomethylated in atheromatous plaque and that the overexpression of EBF1 in HEK293 cells resulted in the increased expression of genes related to cell proliferation (FOXQ1, CCNE1 and PAK1), to inflammatory response (CEBPD), and to cell adhesion (CDH1).…”
Section: Ebf1supporting
confidence: 63%
“…We examined the potential relation of these 33 genes to atherosclerosis, cardiovascular disease, coronary heart disease, or vascular inflammation by searching the PubMed (NCBI) database. Three of the hypomethylated genes (HECA, EBF1 and NOD2) and three of the hypermethylated genes (MAP4K4, ZEB1 and FYN) have previously been implicated in atherosclerosis or cardiovascular disease (10)(11)(12)(13)(14)(15). Immunoblot analysis revealed that the abundance of HECA, EBF1 or NOD2 was markedly increased following the transfection of the HEK293 cells with an expression vector for the corresponding human protein (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The hallmark of NEW in biomedicine is its focus on molecular processes defined by interactions among all molecules that participate in the development of a CCD (13,14). This is in marked contrast to associations between isolated DNA sequence variations or single-target genes and CCDs.…”
Section: Learning More From Gwasmentioning
confidence: 99%
“…The transcriptional profiles of multiple tissues, including liver, skeletal muscle, visceral fat, unaffected arterial wall, and atherosclerosis gathered from CAD patients' bypass surgery. The authors conclude that functionally associated genes cluster in the transendothelial migration of the leukocytes pathways, referred to as the atherosclerosis module, essential for atherosclerosis and CAD development [65]. Taurino C et al analyzed biological pathway miRNA expression, including oxidative phosphorylation and mitochondrial function, and finally, they confirmed the value of gene expression profiling as a promising tool for discovery of CADrelated genes and biologic pathways.…”
mentioning
confidence: 95%